2023
DOI: 10.3390/jcm12031071
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Incidence of Oral Cavity Cancers in the Elderly from 1990 to 2018

Abstract: Objectives: To describe the evolution of the incidence of oral cavity cancers (OCC) among elderly patients in France between 1990 and 2018 and to compare it to the incidence of other cancers sharing the same main risk factors. Material and Methods: The incidence of cancers in mainland France from 1990 to 2018 was estimated from incidence data observed in every cancer registry of the Francim network. Incidence was modeled by a 2-dimensional penalized spline of age and year of diagnosis, associated with a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Following recent findings, there would be other less-studied risk factors (Renou et al, 2023). Among them, oral dysbiosis, Candida spp and HPV infection, chronic mechanical irritation, oxidant diets and others (Gall et al, 2013;La Rosa et al, 2020;Piemonte et al, 2022;Sánchez et al, 2003) are accepted as non-canonical risk factors for OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following recent findings, there would be other less-studied risk factors (Renou et al, 2023). Among them, oral dysbiosis, Candida spp and HPV infection, chronic mechanical irritation, oxidant diets and others (Gall et al, 2013;La Rosa et al, 2020;Piemonte et al, 2022;Sánchez et al, 2003) are accepted as non-canonical risk factors for OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…This situation occurs in Denmark, probably associated with an increase in tobacco consumption among females (Diz et al., 2017). A recent study showed that since 1990, OSCC has been increasing in elderly subjects in France, particularly in women (72%) but alcohol and tobacco consumption alone does not seem to explain this increase (Renou et al., 2023). Figure 2 shows a case of OSCC‐dn in a young woman from Costa Rica without tobacco or alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to assess these mucosal tissues because they are more susceptible to the development of oral cancer, which is more commonly diagnosed in older adults. Early detection of suspicious mucosal lesions by caregivers is critical to avoid compromising general health and quality of life (34).…”
Section: Discussionmentioning
confidence: 99%
“…While the overall incidence of HNSCC continues to decline worldwide, owing to decreased tobacco and alcohol consumption [10,11], oral tongue cancer incidence has been reported to be increasing in several countries [12][13][14]. Interestingly, HPV seems to be involved in only a minor subset of squamous cell carcinomas of the oral cavity [15].…”
Section: Introductionmentioning
confidence: 99%